Knowledge and perceptions of infectious disease physicians about epidemiology, causes, diagnosis, treatment and prevention of Q fever in the Republic of Kazakhstan: results of online survey - Meruyert Bayakhmetova; Gulzhan N. Abuova; Aigerim A. Biniyazova; Yerkin B. Bukharbayev; Timur N. Ablyazimov; Bibigul T. Seitkhanova (National Scientific Medical Center, 2024)
Background: Q fever is a significant zoonotic infectious illness triggered by the pathogen known as Coxiella burnetii, whichcauses severe symptoms when inhaled through the respiratory tract. Serious acute Q fever may cause complications as pneumonia, hepatitis or myocarditis, and some patients may develop chronic Q fever due to incomplete treatment and the topical resistance of C.burnetii. This often requires surgical intervention and anti-infective treatment up to several years, seriously endangering the health of the patients and resulting in the increase of economic burdens. Poor awareness of clinicians about the disease can be one of the reasons for delay intreatment. In view of the above, a survey has been carried out to collect information on the approach of modern Kazakhstani doctorsto the problem of Q fever. Methods: The electronic survey was conducted among infectious disease physicians from different cities of Kazakhstan, based on convenient sampling through social network platforms. Data were collected anonymously between November 14, 2022 and December 14, 2022 among infectious disease doctors. The data collection form consisted of 24 questions including demographic information, general questions about epidemiology, causes, diagnosis, treatment and prevention of Q fever. Duplicate entries were avoided and standard guidelines for reporting Internet surveys were followed. Results: The majority of the respondents (91.7%) considered themselves to have knowledge of information, however 80.2% of physicians showed satisfactory level of knowledge. Westudied the relationship between the proficiency level and various socio-demographic features of the respondents. A statistically significant difference was found in relation of work experience and age (*P<0.05). When comparing the level of knowledge in terms of age categories, it was found that age groups 50-55 years, above 55 yearsshowed significantly more "good" results than other age groups. There were no statistically significant differences in the knowledge level of the participants according to the level of education, gender, place of residence and type of institution (P> 0.05). According to the domains explored, the weakest knowledge was on routes of transmission (39, 32.2%), risk factors of the disease (24, 19.8%), materials used for diagnosis (33, 27.3%), prevention (53, 43.8%), outcomes and complications (33, 27.3%) of Q fever. While there werehigh indicators on the knowledge of sources of infection (87, 71.9%), about the vector (63, 52.1%) and seasonality of the disease (79, 65.3%), symptoms (63, 52.1%), differential diagnosis (73, 60.3%), diagnostic methods (91, 75.2%) and treatment (93, 76.9%). Conclusions: According to the results of the study, the level of experience of infectious disease physicians about Q fever can be assessed as satisfactory. However, the study revealed gaps, especially among young specialists, in the awareness about transmission, risk factors, diagnosis, prevention, outcomes and complications of the disease. We also found that the level of registration of its' diagnosis is low due to the lack of diagnostic testing systems and poor knowledge about the disease in Kazakhstan. As a consequence, we consider it advisable to enhance the level of knowledge about Q fever among young specialists by including comprehensive information in training programs, seminars, conferences in the field of infectiology, epidemiology and public health, as well as expanding diagnostic opportunities in Kazakhstan.